Representation of Bullying Issues in Joe Bell Film (Roland Barthes Semiotics Analysis) - Ricky Ramadhan, Dhimas (Jogjakarta Communication Conference (JCC), 2023)
Bullying is an act of hurting someone that is carried out continuously without any compassion that occurs in society. The representation of the issue of bullying can be seen in several films. One of the films that discuss bullying is the film "Joe Bell". Researchers researched the film "Joe Bell" using descriptive qualitative methods with semiotic theory from Roland Barthes in analyzing data based on the classification of types of bullying. The purpose of this research is to know the representation of bullying issues that occur in the movie "Joe Bell".  The results of this study are that the film "Joe Bell" represents the issue of bullying through scenes, dialogues, and storylines with an emphasis on types of bullying including verbal bullying, physical bullying, and cyberbullying.